Membangun karakter unggul: urgensi pengajaran Akhlak dalam Pendidikan Agama Islam - Dalmeri, Dalmeri; Yuyun Nuriah; Supadi; Mohd Roslan Mohd Nor (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2023)
Islamic religious education in higher education is considered to have failed because it cannot make students have good character and good performance with al-Akhlak al-Karimah. Various parties are trying to develop Islamic Religious Education through teaching morals in higher education. This article explains the orientation of developing Islamic Religious Education through teaching morals in higher education. This research uses a qualitative model to study actual events according to intrinsic categories. There are two models with two approaches to implementing moral teaching, including the aim of Islamic Religious Education to educate students to become religious experts (ulama) and equip them to understand their obligations as Muslims through forming morals. The approach to teaching Islamic Religious Education is to study